3/6f+1/2=6(1/16f-3)

Simple and best practice solution for 3/6f+1/2=6(1/16f-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3/6f+1/2=6(1/16f-3) equation:


f in (-oo:+oo)

(3/6)*f+1/2 = 6*((1/16)*f-3) // - 6*((1/16)*f-3)

(3/6)*f-(6*((1/16)*f-3))+1/2 = 0

(3/6)*f-6*((1/16)*f-3)+1/2 = 0

f/2-6*(1/16*f-3)+1/2 = 0

(-6*2*(1/16*f-3))/2+f/2+1/2 = 0

f-6*2*(1/16*f-3)+1 = 0

1/4*f+1+36 = 0

1/4*f+37 = 0

(1/4*f+37)/2 = 0

(1/4*f+37)/2 = 0 // * 2

1/4*f+37 = 0

1/4*f+37 = 0 // - 37

1/4*f = -37 // : 1/4

f = -37/1/4

f = -148

f = -148

See similar equations:

| 4=-16x | | 0.5(2x-6)=0.5x+1 | | 3s-8=13 | | 196r^2-100= | | 3/8=(7n-10)/(n+2) | | 8x+5=-4x-32 | | -24-1/8p=3/p | | 6x+4=-7x+121 | | 103/4x22/3 | | 2x(-3+4)=8 | | x*x+2=36 | | 5y=-7-2x | | 11+8q=3q-194 | | -3(x-1)+2x=3x-7 | | 21+1/8+2t | | 7/(a-9)=-2/(a+9) | | 4x+4=-2x+52 | | 3s+8=13 | | 30=-g | | 7x+6+3x=56 | | 3x+6=0+2x | | x+6x=49 | | 725-475g=25 | | 7/8+7/4 | | 7=-b/11+4 | | 1+.3w+.5=2w | | x^3-0.9x^2-21.42x=-12.96 | | -7.2c=-28.8 | | -4=23v | | 20-9w=(15-w) | | 1/3j-14=-9 | | x+-3=19 |

Equations solver categories